2016
DOI: 10.1063/1.4972579
|View full text |Cite
|
Sign up to set email alerts
|

Computational screening of core@shell nanoparticles for the hydrogen evolution and oxygen reduction reactions

Abstract: Using density functional theory calculations, a set of candidate nanoparticle catalysts are identified based on reactivity descriptors and segregation energies for the oxygen reduction and hydrogen evolution reactions. Trends in the data were identified by screening over 700 core@shell 2 nm transition metal nanoparticles for each reaction. High activity was found for nanoparticles with noble metal shells and a variety of core metals for both reactions. By screening for activity and stability, we obtain a set o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 21 publications
1
14
0
1
Order By: Relevance
“…Recently nanoframes of Pt 3 Ni 17 and Pt–Ru–M (M = Ni, Fe, or Co) alloys 18 have shown extraordinary results outperforming Pt alone, but Pt remains the basic component of these multi-metallic nanoparticles. In electrocatalysis, density functional theory (DFT) predicts better results for Pt skins 19 , 20 . The use of Pt skins substantially reduces the amount of Pt, but introduces new problems such as difficulties in manipulating the nanoscale elemental distribution 21 and the surface segregation of Pt.…”
Section: Introductionmentioning
confidence: 99%
“…Recently nanoframes of Pt 3 Ni 17 and Pt–Ru–M (M = Ni, Fe, or Co) alloys 18 have shown extraordinary results outperforming Pt alone, but Pt remains the basic component of these multi-metallic nanoparticles. In electrocatalysis, density functional theory (DFT) predicts better results for Pt skins 19 , 20 . The use of Pt skins substantially reduces the amount of Pt, but introduces new problems such as difficulties in manipulating the nanoscale elemental distribution 21 and the surface segregation of Pt.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the volcano plot, it was suggested that the best ORR catalysts should bind *OH slightly weaker (0.1–0.2 eV) than Pt(1 1 1) (highlighted in white in Figure C), and this has been a main framework toward a massive computational screening to develop improved ORR catalysts. Indeed, there are many examples of high‐throughput screening for active ORR catalysts in the literature on this basis . However, we emphasize that the use of the volcano plot with Δ G (*OH) as a single descriptor is valid only if the scaling relation among *O, *OH, and *OOH holds.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, computational calculations of Jiang et al [50] showed partial charge transfer from Ni to Pt in Pt m Ni n alloy clusters, which was supposed to be responsible for the decreased CO poisoning. On the other hand, Corona et al [32] reported the binding energy tuning of oxygen species with Pt for Pt(Ni) core-shell structures, thus increasing the activity for the oxygen reduction reaction. As a result, Ni in Pt(Ni) produces a positive effect in increasing the CO tolerance of Pt.…”
Section: Co Electrooxidationmentioning
confidence: 99%
“…At present, the benchmark catalysts for PEMFCs in the industrial-related applications are carbon-supported Pt and Pt-based alloys [28]. It is generally accepted that alloying Pt with other transition metals allows improving the reaction rates by tuning the d-band structure of the Pt surfaces to lower the bond strength of the Pt-adsorbates, thus leading to better resistance to poisoning [12,[28][29][30][31][32]. Many basic research scientists are currently focusing their attention to obtain catalysts with precursors that provide good electrocatalytic activity using small amounts of noble catalytic metals to lower costs [33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%